2004
DOI: 10.1002/ca.10179
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral occurrence of a chondroepitrochlearis muscle

Abstract: An abnormal muscle slip was encountered during routine dissection studies of a male cadaver. According to its origin, attachment and innervation, the abnormal slip was identified a chondroepitrochlearis muscle. Arterial and nervous supply were from the lateral thoracic artery and the medial pectoral nerve, respectively. Furthermore, no axillary arch muscle was observed. In addition, an abnormality in the attachment of the pectoralis major muscle was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…This distribution would explain why a lesion of C6 causes a paralysis of the sternal portion, whereas a lesion of C5 or C6 does not cause paralysis of the clavicular portion. Conversely, Schumacher (1908) reported the clavicular portion to be innervated by C5, C6, and C7, the superior part of the sternal portion by C6 and C7, the middle one by C6, C7, and the inferior one by C7, C8, and T1.…”
Section: Motor Innervationmentioning
confidence: 99%
See 1 more Smart Citation
“…This distribution would explain why a lesion of C6 causes a paralysis of the sternal portion, whereas a lesion of C5 or C6 does not cause paralysis of the clavicular portion. Conversely, Schumacher (1908) reported the clavicular portion to be innervated by C5, C6, and C7, the superior part of the sternal portion by C6 and C7, the middle one by C6, C7, and the inferior one by C7, C8, and T1.…”
Section: Motor Innervationmentioning
confidence: 99%
“…The chondroepitrochlearis muscle has mainly been reported to be innervated by the MPN (Flaherty et al,1999; Sarikcioglu et al,2004; Jaijesh,2005; Loukas et al,2005; Georgiev and Jelev,2008; Samuel and Vollala,2008; Barcia and Genovés,2009). Spinner et al (1991) reported dual innervation by the MPN and by a nervous branch arising from the confluence between the medial and lateral roots of the median nerve.…”
Section: Pns In Anatomical Variations Of the Pectoral Girdle Musclesmentioning
confidence: 99%
“…An origin from the lateral margin of the pectoralis major muscle has also been reported. However, this anomalous muscle follows a course deviating from this margin and crosses the axilla to be inserted in the medial surface of the humerus, distal to the pectoralis major tendon and usually in the medial epicondyle of the humerus [3,22,23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The insertion of this rare muscular slip is also varied. There are very few reports of occurrence of chondroepitrochlearis muscle in the literature globally (Landry, 1958; Aziz, 1980; Chiba et al ., 1983; Ohtani et al ., 1986; Sarikcioglu et al ., 2004; Loukas et al ., 2005) but there is no report of this rare muscle in the Indian population. This is the first instance of this anomalous muscle to be encountered over a period of 25 years in the dissection hall at Melaka Manipal Medical College, Manipal, India.…”
Section: Introductionmentioning
confidence: 99%